Freedom of pedagogical activity: Contradictions and their solutions - Вazyl, L.; Klymenko, M.; Orlov, V. (Opción, 2019)
The aim of the study is to investigate contradictions of freedom of pedagogical activity and their solutions via theoretical analysis and logical generalization as a method. As a result, the goal-orientation stage in the transformation of vocational and pedagogical activities is conditioned by the presence of value barriers in the definition of targeted guidance on the personal formation of junior pupils. In conclusion, the catalyst for ensuring the pedagogical freedom of the elementary school teacher should be the self-replenishment of its own capabilities and resources to solve educational problems.